Design of switched-capacitor dc-dc converter for battery management system in electric vehicle - Hendika, Fatkhi Nurhuda (2014)
Novel Battery Management System (BMS) for electric vehicle is proposed to enhance system accuracy and reliability with regards to safety issue. Unlike conventional BMS which is done in module level, Embedded System Integrated Circuit (ESIC) is implemented in this design to exclusively control each Lithium-ion battery cell of electric vehicle.